2007
DOI: 10.1007/s10517-007-0410-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial regulation of antagonistic activity of bacteria

Abstract: The phenomenon of microbial regulation of bacterial antagonism was studied using metabolites and cell walls of indicator microorganism culture as inductors. The algorithm of selection of stimulators of bacterial antagonistic activity is determined, experimental conditions are described, and methodological approach to stimulation of bacterial antagonistic activity is developed, which can be used for stimulation of probiotic antagonistic activity and for improving colonization resistance of the host organism dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“… Ullah and Bano (2019) demonstrated that these PGPR have significantly improved the growth and yield of maize grown in saline sodic soil as well physico-chemical properties of soil. Compatibility of these strains was also assessed using a cross streak method ( Semenov et al, 2007 ) on NaCl supplemented LB-medium prior to seed inoculation. Pure saline soil used for the experiment was brought from field area of Biosaline Research Station, Pakka Anna, Faisalabad, Pakistan.…”
Section: Methodsmentioning
confidence: 99%
“… Ullah and Bano (2019) demonstrated that these PGPR have significantly improved the growth and yield of maize grown in saline sodic soil as well physico-chemical properties of soil. Compatibility of these strains was also assessed using a cross streak method ( Semenov et al, 2007 ) on NaCl supplemented LB-medium prior to seed inoculation. Pure saline soil used for the experiment was brought from field area of Biosaline Research Station, Pakka Anna, Faisalabad, Pakistan.…”
Section: Methodsmentioning
confidence: 99%
“…Activity of Bacillus strains against pathogens were studied by the method of delayed antagonism in solid nutrient medium [19]. Briefly, Bacillus strains were inoculated as a line on the surface of a nutrient media.…”
Section: Antagonistic Activity Of Bacillus Strainsmentioning
confidence: 99%
“…In vitro test is a one of the preferred of antagonism test to select probiotics bacteria. Antagonistic activity of bacteria is a prevalent phenomenon which one bacterium species suppresses the development or inhibits the growth of other microorganisms (Semenov et al, 2007). In this study, all potential probionts were identified as Bacillus amyloliquefaciens which were isolated from heamolymph of blue crab.…”
Section: Discussionmentioning
confidence: 97%